Development of E-Student Worksheet Based on Learning Cycle (7e) on Temperature and Heat Material to Improve Understanding of Physics Concepts in High School - Nurfitriani, Ressti; Putri, Desy Hanisa; Medriati, Rosane (Asian Journal of Science Education, 2024)
The facts in the field indicate that students' understanding of physics concepts is still very low. This study aims to describe the feasibility of E-student worksheets based on the Learning Cycle (7e) to improve students' conceptual understanding, describe the level of achievement of students' conceptual understanding, and describe students' responses using Learning E-Student Worksheets based Cycle (7e). This research is a Research and Development (RD) type with the ADDIE method. The research subjects are media experts, material experts, physics learning practitioners, and students of 11th grade Science 3 at Public High School 04 in Bengkulu City. Research instruments consist of interview sheets, observation sheets, needs analysis questionnaires, response questionnaires, expert validation questionnaires, and pretest-posttest questions. Data collection is carried out through interviews, observations, and questionnaires. Data were analyzed using needs analysis, expert validation data, effectiveness of conceptual understanding, and student responses. The research results show that the feasibility of e-Student Worksheets based on the seven e Learning Cycle to improve students' conceptual understanding obtained a score of ninety-seven percent, an increase in conceptual understanding from zero point seven to four, and student responses averaged eighty-seven percent. Based on these results, it can be concluded that the E-Student Worksheet based on the Learning Cycle (7e) is suitable for use and can improve conceptual understanding, as well as receiving very good responses from students